RORγt+ innate lymphoid cells promote lymph node metastasis of breast cancers - Irshad, Sheeba; Flores-Borja, Fabian; Lawler, Katherine; Monypenny, James; Evans, Rachel; Male, Victoria; Gordon, Peter; Cheung, Anthony; Gazinska, Patrycja; Noor, Farzana; Wong, Felix; Grigoriadis, Anita; et al. (American Association for Cancer Research, 2017)
Cancer cells tend to metastasize first to tumor-draining lymph nodes, but the mechanisms mediating cancer cell invasion into the lymphatic vasculature remain little understood. Here, we show that in the human breast tumor microenvironment (TME), the presence of increased numbers of RORγt+ group 3 innate lymphoid cells (ILC3) correlates with an increased likelihood of lymph node metastasis. In a preclinical mouse model of breast cancer, CCL21-mediated recruitment of ILC3 to tumors stimulated the production of the CXCL13 by TME stromal cells, which in turn promoted ILC3–stromal interactions and production of the cancer cell motile factor RANKL. Depleting ILC3 or neutralizing CCL21, CXCL13, or RANKL was sufficient to decrease lymph node metastasis. Our findings establish a role for RORγt+ILC3 in promoting lymphatic metastasis by modulating the local chemokine milieu of cancer cells in the TME.